Memory CD8+ T cells in HIV infection. - Mcmichael, A; Ogg, G; Wilson, J; Callan, M; Hambleton, S; Appay, V; Kelleher, T; Rowland-Jones, S (2000)
Cytotoxic T lymphocytes (CTLs) play a central role in the control of persistent HIV infection in humans. The kinetics and general features of the CTL response are similar to those found during other persisting virus infections in humans. During chronic infection there are commonly between 0.1 and 1.0% of all CD8+ T cells in the blood that are specific for immunodominant virus epitopes, as measured by HLA class I peptide tetramers. These figures are greatly in excess of the numbers found by limiting dilution assays; the discrepancy may arise because in the latter assay, CTLs have to divide many times to be detected and many of the HIV-specific CD8+ T cells circulating in infected persons may be incapable of further division. Many tetramer-positive T cells make interferon-gamma, beta-chemokines and perforin, so are probably functional. It is not known how fast these T cells turn over, but in the absence of antigen they decay in number. Impairment of CTL replacement, because CD4+ T helper cells are depleted by HIV infection, may play a major role in the development of AIDS.